Przyjaźń a subiektywny dobrostan psychiczny adolescentów = Friendship and subjective well-being of adolescents - Wojciechowska, Ludwika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article presents the results of research on the role of friendship in the experience of well-being for adolescents. It was assumed that with a friend can easily run adaptation of adolescent to internal changes, and to social expectations, which in turn will allow them to achieve a sense of accomplishment, self-acceptance and satisfaction with life. We put the question of whether there is a link between the experience of friendship and mental well-being of adolescents.
Keywords: przyjaźń; adolescencja; dobrostan psychiczny; friendship; adolescence; subjective well-being